ENHANCED APPROACH FOR CHANGE OF COURSE OF STUDY USING FUZZY LOGIC (FUDMA JOURNAL OF SCIENCES, 2024)
In tertiary institutions of Nigeria, students are admitted through the Unified Tertiary Matriculation Examination (UTME) to study courses of their choice. However, most students often perform poorly. Thus, the need to change their programme of study becomes a necessity or risk being withdrawn from the university. The student for a change of programme is required to present a cumulative grade point average (CGPA), which informs the student’s status and commonly used criteria to determine the student’s qualification for a change of programme of study. The students are allowed to choose or advised which programme to choose based on their perceived strength. This is not scientific and have proven ineffective since may be based on biased perception. Thus, most of these students still perform poorly in the new programme of study and may end up being withdrawn. In order to minimize subjectivity and handle uncertainty in such a decision process, this paper proposed a fuzzy logic approach for the change of programme of study by considering the student’s Senior Secondary School Certificate Examination (SSCE) result(s), UTME scores, and grades obtained in the various examined and related courses. The CGPA initiates the entire process. The simulation was done in MATLAB, inputs were supplied and the recommendation is generated. The strength values of each input is calibrated from, as   from which the system recommends other faculties, Computer Science, Statistics, Physics and mathematics respectively. The system enhances the chance that a student may perform in their newly proposed programme.
Keywords: CGPA; Change of Course; Fuzzy Logic; Fuzzy Set; SSCE; UTME